Effect of Li+/Na+ exchange on mechanical behavior and biological activity of lithium disilicate glass-ceramic. (February 2022) - Li, X.C.; Li, D.; Zhang, S.F.; Jing, L.; Zhou, W.H.; He, L.; Yu, S.; Meng, M.
Abstract: Lithium disilicate (LD) glass-ceramics with a stoichiometric composition were ion-exchanged in pure NaNO3 or mixed NaNO3  + KNO3 molten salt baths below the glass transition temperature ( T g ). The microstructures, surface morphologies, mechanical properties and bioactivities of the ion-exchanged glass-ceramics were studied in detail. It was found that the strength and toughness of LD glass-ceramic could be enhanced from 175 MPa to 0.96 MPa m 1/2 before ion-exchange to 546 MPa and 4.31 MPa m 1/2 respectively under a lowered ion-exchange temperature because the less stress relaxation. In addition, a gradient of Na + rich layer in the surface of glass-ceramic was induced by Li + /Na + exchange, which could be beneficial to the formation of HA (Hydroxyapatite) with nano-size porous after soaking in SBF (Simulated Body Fluid) solution and exhibited better bioactivity compared with the original LD glass-ceramic. The results might provide a reference for the strengthening and biological activation of LD glass-ceramics in bone restoration applications. Graphical abstract: Image 1 Highlights: LD glass-ceramic can be significantly strengthened and toughened after ion-exchange treatment. A less stress relaxation when ion-exchange under a lower temperature. LD glass-ceramic shows good biological activation after ion-exchange treatment. Ion-exchange treatment can inhibit the initiation and propagation of cracks in LD glass-ceramic.